2018
DOI: 10.1073/pnas.1716266115
|View full text |Cite|
|
Sign up to set email alerts
|

Chimeric antigen receptor T cells form nonclassical and potent immune synapses driving rapid cytotoxicity

Abstract: Chimeric antigen receptor T (CAR-T) cells are effective serial killers with a faster off-rate from dying tumor cells than CAR-T cells binding target cells through their T cell receptor (TCR). Here we explored the functional consequences of CAR-mediated signaling using a dual-specific CAR-T cell, where the same cell was triggered via TCR (tcrCTL) or CAR (carCTL). The carCTL immune synapse lacked distinct LFA-1 adhesion rings and was less reliant on LFA to form stable conjugates with target cells. carCTL recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
231
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(265 citation statements)
references
References 47 publications
11
231
0
4
Order By: Relevance
“…Finally, the central SMAC (cSMAC) is the site where cytotoxic granules are delivered in a polarized fashion toward the target cell and TCR‐signaling is terminated . Compared with TCRs, ligation of a CAR results in disorganized antigen receptor and signaling molecule clusters characterized by the punctate accumulation of Lck . Downstream signal transduction with a CAR is rapid, transient, and less dependent on LFA‐1 relative to a TCR.…”
Section: Cars and Tcrs Are Structurally And Biophysically Distinct Anmentioning
confidence: 99%
“…Finally, the central SMAC (cSMAC) is the site where cytotoxic granules are delivered in a polarized fashion toward the target cell and TCR‐signaling is terminated . Compared with TCRs, ligation of a CAR results in disorganized antigen receptor and signaling molecule clusters characterized by the punctate accumulation of Lck . Downstream signal transduction with a CAR is rapid, transient, and less dependent on LFA‐1 relative to a TCR.…”
Section: Cars and Tcrs Are Structurally And Biophysically Distinct Anmentioning
confidence: 99%
“…Remarkably, this less organized synapse correlated with the ability of the CAR to induce quicker recruitment of cytolytic granules to the membrane and faster degranulation . Despite the higher affinity of CARs for their cognate antigen, the dwell‐time of a CAR T cell with its target was found to be less than that of a T cell recognizing its cognate antigen through the TCR, potentially due to the incomplete formation of a stabilizing immune synapse . While the structural and physical differences of CARs and TCRs could account for some level of this discrepancy, the formation of the CAR synapse seems to be guided in part by the signaling of the engaged receptor, as “inside‐out” signaling is well‐described for TCR‐driven immune synapses and differences in CAR‐ and TCR‐signal transduction have been observed in T cells .…”
Section: Antigen Low Escape and Car T Cell Activationmentioning
confidence: 99%
“…While the TCR synapse has been extensively studied, substantially fewer studies have been undertaken to describe the CAR synapse. As opposed to the TCR synapse, CAR synapses demonstrate significantly less organization with more diffuse interfaces with target cells . In studies directly comparing the immune synapse of a TCR vs that of a CAR within the same T cells, Davenport et al demonstrated the CAR synapse was unable to replicate the organization of LFA‐1, actin, and Lck that was induced upon TCR activation .…”
Section: Antigen Low Escape and Car T Cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Although there are clearly morphological and functional differences between the synapses formed by CAR and those formed by the TCR (Davenport et al 2018), the distance between two cells is still thought to play a key role in the activation of CAR-T cells Rodgers et al 2016). For example, it Comparison of the cell-to-cell distance created by TCR vs CAR.…”
Section: Targeting Domainmentioning
confidence: 99%